Relationship between long jump and triple jump distances and the performance in running, jumping and strength tests - Felipe José Aidar; Antônio José Silva; André Luiz Carneiro; Rui Cabral; Victor Machado Reis (Universidade Federal de Santa Catarina, 2006)
The use of test batteries is the most common procedure to assess the specific preparation status of athletes. This procedure is also observed in the case of horizontal jumpers (long and triple jump). The aim of the present study was to investigate the associations between the performance in the long jump and in the triple jump and the performance in running, jumping and strength tests. Forty-five male physical education students performed competitions in long jump and triple jump after a month of technique learning. A week later, they were submitted to the following tests: 1) 20 m maximum-speed running (20m); 2) standing long jump; 3) standing triple jump with alternate legs (TS); 4) maximum and mean isometric strength; 5) Squat Jump; 6) Counter Movement Jump; 7) Drop Jump. The 20m and the TS were the tests that showed a larger association with the competitive performance in the horizontal jumps and, altogether, they were able to explain about 50% of the variance of the results in the long jump and in the triple jump. We conclude that the 20m and the TS can be used to predict the performance of novices in the long jump and in the triple jump with an acceptable error (»6% e »4%, respectively). The results also suggest that running and horizontal jumping field tests are preferable than laboratory tests to assess the jumper's fitness. ABSTRACT A aplicação de baterias de testes é o meio mais usual para avaliar o estado de forma de atletas de diversas especialidades. Assim sucede com os especialistas de saltos horizontais (salto em comprimento e triplo salto). O objectivo do presente estudo foi investigar a relação entre a prestação no Salto em Comprimento e no Triplo Salto e o desempenho em testes de corrida, impulsão e força isométrica. Quarenta e cinco estudantes de educação física do sexo masculino realizaram duas competições, uma de salto em comprimento e outra de triplo salto. Na semana seguinte foram submetidos aos seguintes testes: 1) 20 m de corrida com balanço prévio (20m); 2) impulsão horizontal a pés juntos; 3) triplo salto com apoios alternados e partida parada (TS); 4) teste de força máxima isométrica e de força média isométrica; 5) Squat Jump; 6) Counter Movement Jump; 7) Drop Jump. Os testes de 20m e de TS foram os que demonstraram maior grau de associação com a prestação competitiva nos saltos horizontais e permitiram, em conjunto, explicar cerca de 50% da variância do resultado no triplo salto e no salto em comprimento. Concluímos que os testes de 20m e de TS podem ser usados para predizer a prestação de iniciantes no salto em comprimento e no triplo salto com um erro de predição da prestação aceitável (»6% e »4%, respectivamente). Os resultados também sugerem que testes de terreno de corrida e de impulsão horizontal são preferíveis aos testes de laboratório para avaliar a aptidão de saltadores